Endoscopic Endonasal Pituitary Surgery: Outcome analysis of 32 cases - Islam, Md Rafiqul; Ahmed, Monsur; Hasan, Md Rashidul; Mehbub, Hasan; Ashfaq, Musannah (Bangladesh Journal of Neurosurgery, 2021)
Introduction: Microsurgical trans-sphenoidal surgery for pituitary tumors has been standard treatment for nearly of century and was established by Harvey Cushing in the early twentieth century. Today, endoscopy is increasingly accepted in the treatment of pituitary lesions. In this article we analysed the surgical technique and outcome of 32 patients retrospectively with pituitary lesions treated with endoscopic endonasal trans-sphenoidal approach. Material & Methods: Between January 2016 to July 2020, 32 patients (22 female and 10 male) with pituitary tumors were operated using endoscopic endonasal transsphenoidal procedure without any nasal speculum. Post-operative nasal packing given in both nostril in all cases. The follow-up period ranged from 3 to 24 months. Results: Among the 32 patients gross total tumor removal was achieved in 23 cases (71.87%), subtotal removal done in 9 cases (28.13%). Post-operative discomfort was minimal and hospitalization was 7–10 days. 10 patients developed post-operative transient diabetes insipidus, among them persisting DI occur 2 patients for further 3 months. No patient died in our series within follow up period. Conclusion: Endoscopic endonasal trans-sphenoidal approach for removing pituitary lesions is a form of minimally invasive skull base surgery with excellent post-operative results. Bang. J Neurosurgery 2021; 10(2): 185-191